Genetic diversity and structure of Pocillopora spp. corals in the Gulf of Papagayo, Costa Rica - Hidalgo Sánchez, Randall (2025)
Understanding the genetic diversity and connectivity of coral populations is necessary for their adequate management, especially considering global climate change. This study reports the genetic diversity and structure of the most common coral genus in the Eastern Tropical Pacific, Pocillopora. A total of 12 microsatellite loci were tested to estimate genetic diversity metrics for three populations in the Gulf of Papagayo, of which 11 amplified successfully. High level of clonality was found in one of the populations (Jícaro; clonal richness, R = 0.069), where only three multilocus genotypes (MLGs) were found. This population also exhibited the lowest heterozygosity (He = 0.364) compared to Matapalo (He = 0.624) and Zapotillal (He = 0.598). Genetic structure was assessed using Nei’s pairwise FST and complemented with assignment tests. The analyses found Jícaro to be differentiated from both Matapalo and Zapotillal; whereas the last two populations show reduced divergence between them. These results indicate predominant asexual reproduction in Jícaro. Coupled with genetic isolation with the other sites suggest the occurrence of different Pocillopora species. Anyhow, they highlight a reduced genetic diversity, and thus a high vulnerability, in Jícaro.